REVISING THE PROJECT OF MODERNITY HERMENEUTICS - Marius Povilas Povilas Šaulauskas (Problemos)
The article is intended to argue the fundamental modernity of Habermasian, Gadamerian and, to a considerable extent, Rortian philosophical projects in spite of their "self-limiting" and thereby "transcending" modern metanarrative characteristics. An indispensable presupposition of the Cartesian epistemology could be interpreted capitalizing on Haber-masian concept of performative individuality and communicative action. As with the hermeneutical situation of Rousseau’s confession, cartesian episte-mological Ego always posits itself in terms of simultaneously naming and reflecting action that is always performed in the face of (real or simulated) second-person audience. The self-accountable realization of being epistemologically alone goes hand-to-hand with the necessary existence of the (one or many) Other-You, be it the Almighty, society or History. Therefore the (cartesian) epistemological performative stand is indispensable in attributing an independent variable status both to modern subjec-tivity (as articulated by Descartes and Schleiermacher) or "post-modern" intersubjectivity. The latter is advocated, their quarrel notwithstanding, by Gadamer and Habermas, as well as by various other approaches, intended to break through the boundaries of modern philosophy, e.g. by the herme-neutical pragmaticism of Richard Rorty.